(untitled) (Al-Qamar, 2022)
To live a worthwhile life, a long-term vision is very important for a person and a nation, as well. Allah Almighty gave a clear vision to humanity which is called ‘abdiyah” i.e. slavery of Allah”, which means to live life on this planet in accordance with Allah’s commandments. Along with this obedience we Muslims are responsible to preach the final word of God all over the world. But unfortunately, we are the most visionless nation of the world in current scenario. As, from centuries we are not connected with Qur’an and Sunnah and we have not practically accepted them as code of life so we are being used as tools for actualization of Jewish and Christian vision. Infact their interests are driving force for us as we are living a worldly material driven life instead of a meaningful and purpose driven life. This paper deals with importance of divinely vision, connecting ourselves and others with Allah (swt).